Teachers views about the preparation of questions for question bank on the basis of subject content for the formative assessment of the department. (Bangladesh Journal of Medical Education, 2021)
This descriptive type of cross-sectional study was conducted to find out the teachers views about the preparation of questions for question bank on the basis of subject content for the formative assessment of the department. The study was conducted in four government and four non-government dental colleges. The teachers of the selected dental colleges were the study population and sample size was total of a 165 in which were 53 head of the department and 112 lecturers. Data was collected from the teachers with a self-administered semi-structured questionnaire and analyzed by using SPSS 19. The questionnaire included different types of opinion about the question bank. In this study, tried to extract the information mainly about how a full phased question bank works in a dental college including question pattern and answer key preparation, moderation & constant development of the question bank, key personnel who directly involved with question preparation. Faculty members expressed their valuable opinions about different types of formative questions where it was found that Assistant Professors were closely involved with question preparation rather than other faculty members. The study also explores that even if formative questions were well prepared but lack of standard answers, rating scales and accepted checklist made the ultimate process of accessing question bank becomes challenging to conduct specific exams.Bangladesh Journal of Medical Education Vol.12(2) July 2021: 23-29